Copper finds from the Ljubljansko barje (Ljubljana Moor) – a contribution to the study of prehistoric metallurgy* - Trampuž Orel, Neva; J. Heath, David (Arheološki vestnik, 2008)
The metal composition of a group of eneolithic copper artefacts from the Ljubljansko barje (Ljubljana Moor) was determined by ICP-AES analysis. Half of the finds come from nineteenth century excavations of prehistoric pile dwellings at Ig and the remaining objects were found on the bed of the River Ljubljanica in the twentieth century. The material has been approximately dated to the fourth and third millennia BC. Analysis showed that all the objects are made of copper with various impurity patterns differing in terms of the concentration ratios of arsenic, antimony, nickel, silver and lead. The majority of the artefacts are of a copper type with dominant antimony, copper with domi-nant arsenic was found only in two artefacts. All artefacts also contain lead and silver as trace elements. The results showed that the classification of the metal composition into the copper types that have been identified in the recent German research by means of multivariate analysis was reasonable.